Exploring ICT Indicators for ‘Smart Cities’ in Nepal: Lalitpur Metropolitan City - Karki, Arjun; Dahal, Sudhamshu (International Journal of Social Sciences and Management, 2020)
The study explores the existing technological infrastructure in the proposed 'smart cities' in Nepal. It follows the proponents of structural existence and interactivity patterns according to the Structuration Theory by Anthony Giddens (1991). This study incorporating qualitative as well as quantitative data has attempted to compare the digital status of Nepal with Asian and South Asian countries. It is found that local administrations in towns and in villages are continuously working to bring their areas under connection by the installation of CCTVs, smart poles, smart maps, internet infrastructure and other ICT infrastructure. The study used content analysis of documents and survey conducted in Lalitpur Metropolitan City (LMC). The study recommends the four main areas viz., strict policies and practicable guidelines/directives; installation of ICT infrastructure; implanting skill and ICT qualified human resources and construction of robust websites. If the Government of Nepal works in these four areas then the country will step in the track of formation of ‘smart cities’ in Nepal. Int. J. Soc. Sc. Manage. Vol. 7, Issue-1: 1-11